The cell polarity protein MPP5/PALS1 controls the subcellular localization of the oncogenes YAP and TAZ in liver cancer - Tóth, Marcell; Wan, Shan; Schmitt, Jennifer; Birner, Patrizia; Wei, Teng; Bubnoff, Fabian von; Torre, Carolina de la; Thomann, Stefan; Pinna, Federico; Schirmacher, Peter; Weiler, Sofia Maria Elisabeth; Breuhahn, Kai (International journal of molecular sciences, 2025)
The oncogenes yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) are potent liver oncogenes. Because gene mutations cannot fully explain their nuclear enrichment, we aim to understand which mechanisms cause YAP/TAZ activation in liver cancer cells. The combination of proteomics and functional screening identified numerous apical cell polarity complex proteins interacting with YAP and TAZ. Co-immunoprecipitation (Co-IP) experiments confirmed that membrane protein palmitoylated 5 (MPP5; synonym: PALS1) physically interacts with YAP and TAZ. After removing different MPP5 protein domains, Co-IP analyses revealed that the PDZ domain plays a crucial role in YAP binding. The interaction between YAP and MPP5 in the cytoplasm of cancer cells was demonstrated by proximity ligation assays (PLAs). In human hepatocellular carcinoma (HCC) tissues, a reduction in apical MPP5 expression was observed, correlating with the nuclear accumulation of YAP and TAZ. Expression data analysis illustrated that MPP5 is inversely associated with YAP/TAZ target gene signatures in human HCCs. Low MPP5 levels define an HCC patient group with a poor clinical outcome. In summary, MPP5 facilitates the nuclear exclusion of YAP and TAZ in liver cancer. This qualifies MPP5 as a potential tumor-suppressor gene and explains how changes in cell polarity can foster tumorigenesis.